Genomic insights into methicillin-resistant Staphylococcus pseudintermedius isolates from dogs and humans of the same sequence types reveals diversity in prophages and pathogenicity islands. - Nathita Phumthanakorn (Public Library of Science (PLoS), 2021)
Methicillin-resistant Staphylococcus pseudintermedius (MRSP) is an important opportunistic pathogenic bacterium of dogs that also occasionally colonize and infect humans. However, whether MRSP can adapt to human hosts is not clear and whole genome sequences of MRSP from humans are still limited. Genomic comparative analyses of 3 couples of isolates from dogs (n = 3) and humans (n = 3) belonging to ST45, ST112, and ST181, the dominant clones in Thailand were conducted to determine the degree of similarities between human and animal MRSP of a same ST. Among eight prophages, three prophages associated with the leucocidins genes (lukF/S-I), φVB88-Pro1, φVB16-Pro1 and φAP20-Pro1, were distributed in the human MRSPs, while their remnants, φAH18-Pro1, were located in the dog MRSPs. A novel composite pathogenicity island, named SpPI-181, containing two integrase genes was identified in the ST181 isolates. The distribution of the integrase genes of the eight prophages and SpPI-181 was also analysed by PCR in 77 additional MRSP isolates belonging to different STs. The PCR screen revealed diversity in prophage carriage, especially in ST45 isolates. Prophage φAK9-Pro1 was only observed in ST112 isolates from dogs and SpPI-181 was found associated with ST181 clonal lineage. Among the 3 couple of isolates, ST45 strains showed the highest number of single nucleotide polymorphisms (SNP) in their core genomes (3,612 SNPs). The genomic diversity of ST45 isolates suggested a high level of adaptation that may lead to different host colonization of successful clones. This finding provided data on the genomic differences of MRSP associated with colonization and adaption to different hosts.